2013
DOI: 10.1155/2013/761675
|View full text |Cite
|
Sign up to set email alerts
|

Benzophenone Suppression of Quercetin Antioxidant Activity towards Lipids under UV‐B Irradiation Regime: Detection by HPLC Chromatography

Abstract: Quercetin, a well-known flavonoid antioxidant, has been employed to control benzophenone-sensitized peroxidation of the lipid mixture in methanol solution, induced by continuous UV-B irradiation. Surprisingly, the detected quercetin antioxidant activity was almost negligible. The presented data suggests that the reason is not in its own UV-B-induced degradation but rather in its interrelationship with benzophenone during UV-B stress. On the other side of this relationship, benzophenone anticipated sensitizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Thus, UV-B induced changes of the QC-BZP-PL90 mixture studied by HPLC chromatography allowed a kinetic analysis of clearly separated species [30]. Isocratic elution of the mixture with methanol as a mobile phase gave chromatograms recorded at absorption maxima of the separated components: QC, tret.…”
Section: Uv-b Induced Bleaching Of Qc In Qc-bzp Mixturementioning
confidence: 99%
See 3 more Smart Citations
“…Thus, UV-B induced changes of the QC-BZP-PL90 mixture studied by HPLC chromatography allowed a kinetic analysis of clearly separated species [30]. Isocratic elution of the mixture with methanol as a mobile phase gave chromatograms recorded at absorption maxima of the separated components: QC, tret.…”
Section: Uv-b Induced Bleaching Of Qc In Qc-bzp Mixturementioning
confidence: 99%
“…Also, two isosbestic points at λ = 273 nm and λ = 322 nm indicate the formation of at least one degradation product. By comparing QC degradation rates in the absence (QC-PL90) and in the presence of BZP (QC-BZP-PL90), it was evident that BZP accelerates QC degradation up to 10 times [30]. It was concluded that suppression of QC antioxidant activity on one side, and the inhibition of BZP sensitizing activity on the other is somehow related to BZP( 3 BZP)-QC mutual interaction.…”
Section: Uv-b Induced Bleaching Of Qc In Qc-bzp Mixturementioning
confidence: 99%
See 2 more Smart Citations